Together but Not Mixed: Mistletoe Genetic Diversity and Seed Disperser Activity Between Evergreen and Deciduous Forests - Rodriguez-Gomez, G (Elsevier GmbH, 2025)
Habitat structure plays an important role in determining forest mammals abundance and activity patterns, impacting their interactions with plant species. In the southern South American temperate rainforests, two mistletoe species (Tristerix corymbosus and Desmaria mutabilis) depend on the arboreal marsupial Dromiciops bozinovici for seed dispersal, inhabiting a mosaic of evergreen and deciduous Nothofagus-Araucaria forests. We used camera traps to compare marsupial abundance, visitation rates, and daily activity patterns between evergreen and deciduous forests. Also, we sequenced DNA (using SNPs) from both mistletoes to assess their genetic diversity, population genetic structure, and landscape genetics. Dromiciops bozinovici visited T. corymbosus more frequently in the evergreen forest and D. mutabilis in the deciduous forest, as it is the only mistletoe species found above 1250 m of elevation. Both mistletoe species showed similar genetic diversity between forest types, but T. corymbosus was more diverse than D. mutabilis; population structure was weak but significant in both cases. In both cases, gene flow was stronger towards the evergreen forest, and this asymmetry was more pronounced for D. mutabilis. Also, geographic and genetic distances were positively correlated except for D. mutabilis in the deciduous forest. Dromiciops bozinovici activity and abundance varied according to forest type and mistletoe species associated, which seem to be influencing gene flow and genetic diversity patterns. Interaction between plants and frugivores is particularly relevant in high-mountain forests, where mistletoes provide major resources for frugivores, which shape their spatial and genetic structures. © 2025 Elsevier GmbH